Islamic Inheritance Law in Indonesia: Analysis of Legal Implementation and Compliance Among Muslim Communities - Safitri, Ella; Ahmat Saiful (Yayasan Insan Mulia Bima, 2025)
This research discusses the implementation of Islamic Inheritance Law for Muslims in Indonesia, which in its application is still not fully implemented for Muslim heirs. When referring to the Law, Muslim heirs are obliged to divide the inheritance property by Islamic law, but in practice in Indonesia, many heirs still use customary law and civil law (Burgerlijk Wetboek) based on various reasons. The purpose of this research is to find out the implementation of Islamic Inheritance Law for the Muslim Population in Indonesia. This research method uses the Law approach method, which is carried out by analyzing various laws and regulations related to the field of Inheritance Law. Based on the results of the research, Islamic Inheritance Law cannot be implemented in Indonesia for the Muslim population because Indonesian society is still influenced by customary inheritance law, either following the individual-patrilinial, matrilineal or bilateral-collective inheritance system. Apart from the strong influence of tradition or customary law, another obstacle is that Muslims do not fully understand the concept of justice and equality in Islamic inheritance law, especially when it comes to the portion of sons and daughters. It is necessary to formulate a national inheritance law system by taking into account the general principles of inheritance and accommodating each inheritance law system in the country.